POLA KOMUNIKASI GURU DALAM MEMBIMBING SISWA UNDERACHIEVER DI MI AL-UMMAH DESA SUKAMAJU KECAMATAN SINGINGI HILIR - Siti Isnaningsih; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The problem of learning diffilcuties experienced by students is a very important problem that needs to get serious attention from educators.underachiever is one of the problems in the world of education to be overcome,whereas in overcoming it requires all parties, especially in this case the educators.this problem still often arises, because the potentials that exist in students cannot develop optimally.students who are said to be underachievers are students who have a high of intelligencr but their learning achievement is low (below average). The purpose of this study was to determine one-way communication patterns, two-way communication patterns, and multiple-way communication patterns of teachers in guilding underachiever students at MI Al-Ummah sukamaju village, singing downstream district, as well as to determine the difficulties for underachiever students. At MI Al-Ummah sukamaju village, singing downstream district. The research method used in this study is a qualitative method with a descriptive approach. In this study, the research location was carried out at MI Al-Ummah sukamaju village, singingi downstream district. When the research was carried out for approximately 4 months, the subjects in this study were the principal, class teacher, homeroom teacher, and students in grades 6. And the objects of this research were one-way communication patterns, two-way communication patterns, and communication patterns. There are many teacher directions in guiding underachiever students at MI Al-Ummah sukamaju village, singing downstream district. Types and sources of data in this study using primary data and secondary data, data collection techniques using observation. Data analysis techniques according to Miles and Huberman,namely data reduction, data presentation, and conclusion drawing. And the technique of checking the validity of the data using the technique of extension of participation, and triangulation. The results of research on one-way communication patterns carried out by teachers are carried out formally and informally. One-way communication where the teacher explains while the students are passive.in this one-way communication it is more to the lecture method only, where the teacher explains the material, and there is no student response.a two-way communication pattern, where in this two-way communication there is reciprocity, good responses from some students, and in this communication the teacher uses a method by displaying animations that refer to pancasila,ethnicity and culture in Indonesia and religion, which is the story in the history of the prophet, the procedures for prayer and ablution. After that the teacher explains a little and then asks students about what things can be taken from the animation.multidirectional communication patterns, where in this multidirectional communication the teacher gives material and assignment to students in group, so that they can work together to exchange ideas aMnd exchange opinions.